Empoasca (Kybos) ivcifiovi sp. n. — новый вид цикадок (Homoptera, Cicadellidae) с Украины - Логвиненко, В.Н. (Вестник зоологии, 1980)
Empoasca (Kybos) ivanovi sp. n. from the north-western part of the Ukraine, a new representative of Typhlocybinae, is the closest to E. (K.) calyculus C e r., but it clearly differs from the latter in the nonextended serrate part of the style, sharply narrowed and drawn off apex of the anal tube processes, intensively developed apodema and the presence of a sclerotized band behind the dorsal apodemas.